Assessment of elevated road traffic pollution on roadside trees and vegetation in urban environments - Chauhan, Avnish; Pandey, Gaurav; Singh, Man Vir; Sethi, Muneesh; Gururani, Prateek; Awasthi, Amit; Chaube, Shshank; Lodh, Abhishek (Frontiers in Environmental Science, 2025)
Road traffic pollution is one of the most important factors among other environmental factors that influence the roadside vegetation. The present research examines the impact of motorway flyovers and at-grade roads on air pollution (PM10, SOx, NOx, and air quality index (AQI)) and roadside vegetation in Dehradun by considering the important biochemical parameters such as chlorophyll, ascorbic acid, leaf pH, and the air pollution tolerance index (APTI). Five varieties of plants were selected along the busiest highway in Dehradun, including Mangifera indica (mango) and four varieties of bougainvillea in red, pink, gold, and white colors. The monthly monitoring of PM10, SOx, and NOx concentrations during the study period showed significant seasonal variations at all three sites. Maximum PM10 (58 μg/m3) and NOx (33 μg/m3) were observed at Site 2 (on-flyover) during December 2024, while the highest air quality index (AQI) value at this site was 270. Regression analysis showed that the AQI trends from winter to spring declined, and Site 2 experienced the greatest monthly reduction (−13.25 units month-1; R2 = 0.88). PM10 and NOx were the most influential factors about AQI (r = 1.00 and r = 0.90), indicating that these pollutants are a major component of urban pollution. Biochemical parameters were used as markers to assess the responses to pollution in mango and bougainvillea (red, white, pink, and gold varieties). Mango showed a higher tolerance (APTI 8.09) than bougainvillea varieties, where the maximum stress was caused (APTI up to 4.65) and also exhibited a marked reduction in the levels of chlorophyll and ascorbic acid. Results show meteorological emission effects on urban air quality, supporting plant-based biomonitoring programs.